Analysis of students learning interest in biology subject matter of viruses in grade X senior high school - Muhammad Taufik Amin; Risma Delima Harahap (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Virus concept biology subjects whose material is abstract in nature can generally reduce students' interest in learning. Students' interest in learning affects their learning outcomes both academically and non-academically. This study aims to analyze the learning interests of students at SMA Negeri 2 Bilah Hilir in the subject of virus concept biology. The samples in this study were students in class X MIA-1 and X MIA-2 with a total of 65 people. This type of research is qualitative research. The data collection technique uses a questionnaire of students' learning interest, and interviews as supporting data. The results showed that the indicators of students' feelings of pleasure in participating in learning were as large as and the involvement of students in learning received the